2020
DOI: 10.1177/0003319720939467
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Mesenchymal Stem Cells in the Treatment of Diabetic Foot Ulcers: A Review of Preclinical and Clinical Studies

Abstract: This review provides an outline of the use of adipose-derived mesenchymal stem cells (AMSCs) in the treatment of diabetic foot ulcers (DFUs). A systematic search of PubMed and the Cochrane database was performed on October 2, 2019. Eighteen studies were identified (14 preclinical and 4 clinical). Studies in animal models have demonstrated that AMSCs enhance diabetic wound healing, accelerate granulation tissue formation, and increase reepithelialization and neovascularization. Only 1 randomized control trial h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 78 publications
(115 reference statements)
0
13
0
Order By: Relevance
“…Diabetic wound healing can be promoted by ASCs seeded in Pluronic F‐127 hydrogels 21 . ASCs promote granulation tissue formation and facilitate diabetic wound healing 24 . Furthermore, ASCs have been shown to improve wound healing through promoting collagen synthesis 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic wound healing can be promoted by ASCs seeded in Pluronic F‐127 hydrogels 21 . ASCs promote granulation tissue formation and facilitate diabetic wound healing 24 . Furthermore, ASCs have been shown to improve wound healing through promoting collagen synthesis 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Since AMSCs are harvested from autologous adult fat, fewer ethical controversies exist [ 95 ]. In addition, several studies have shown that AMSCs are able to promote wound healing via increasing epithelization and granulation tissue formation, via their anti-inflammatory and anti-apoptotic effects, and through the release of angiogenic cytokines [ 96 , 97 ]. A study by Cianfarani et al reported that diabetes mellitus impairs the function of AMSCs and alters their intrinsic properties, which affects their healing properties in DFU in diabetic rat models [ 98 ].…”
Section: Stem Cell Therapymentioning
confidence: 99%
“…Moreover, studies assessing wound healing have reported beneficial effects of adding platelet-rich plasma to AMSCs, specifically acting as a powerful paracrine effector and cell carrier to increase the potential of transplanted cells used in therapies [ 102 ]. In addition to diabetes, obesity and aging negatively impact AMSCs, impairing their function and properties including angiogenesis, multipotent state, differentiation, metabolism, and immunomodulation [ 95 , 97 , 103 , 104 , 105 ]. As a result, it can be deduced that employing allogeneic normal AMSCs rather than autologous, diabetic, and impaired ones is a better alternative in cell therapy to promote wound healing in diabetic patients [ 99 ].…”
Section: Stem Cell Therapymentioning
confidence: 99%
“…16 A larger multicenter trial would be required to confirm the present results. 30 The impact of the LOS reduction on the overall costs of care represents an additional point of interest for health care providers. Future investigations are required on this specific topic.…”
Section: Limitations Of the Studymentioning
confidence: 99%